1995
DOI: 10.1111/j.1532-5415.1995.tb07196.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Differences in the Utilization of Therapies Post Acute Myocardial Infarction

Abstract: A surprisingly high percentage of those older than age 65 received invasive tests and interventions. This high utilization rate coexists with our continued ignorance about the efficacy of these tests and interventions in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…In addition, there was evidence for the underutilization of aspirin in our older patients. This is in accordance with numerous studies reporting the underutilization of proven effective therapies, in particular aspirin and beta‐blockers 28–31 …”
Section: Discussionsupporting
confidence: 90%
“…In addition, there was evidence for the underutilization of aspirin in our older patients. This is in accordance with numerous studies reporting the underutilization of proven effective therapies, in particular aspirin and beta‐blockers 28–31 …”
Section: Discussionsupporting
confidence: 90%
“…However, nonclinical factors such as age and sex also affected patterns of receipt of these medications. Patients who were older (Ն75 years) were significantly less likely to use any of the 3 medications, a finding consistent with previous studies that show underuse of ␤-blockers [20][21][22] and aspirin 17 in elderly patients at hospital discharge after AMI. Yet, the survival benefit from ␤-blocker 21,39 and aspirin 1 therapy in patients with established coronary heart disease appears to be at least as great for elderly as nonelderly patients.…”
Section: Commentsupporting
confidence: 89%
“…Results of well-designed clinical trials have been shown to affect the prescription of cardiovascular medications by physicians. 28,33 However, results of several previous studies conducted in the 1990s found significant underuse of aspirin [17][18][19] and ␤-blockers 18,20-23 at hospital discharge after an initial AMI despite the demonstrated efficacy of these medications in published clinical trials. Undertreatment of hypercholesterolemia among patients with established coronary heart disease also has been previously described.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] At discharge, as many as 80% of post-MI patients should be treated with β-blockers. 9 However, an analysis of nationwide prescribing patterns following hospital discharges showed that less than 40% of MI patients received β-blockers for secondary prevention of recurrent MI.…”
mentioning
confidence: 99%